Ovariohysterectomy: A Salvage Method in Welfare of Stray Cattle: A Clinical Case Report of Five Animals - Borakhatariya, DN; Karangiya, VK; Ribadiya, NK (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
With the hike of the human population in metro cities, problems of stray orphan cattle have also increased simultaneously. Such animals when feeding on roadside litter and plastic garbage, don’t gain optimum nutrition and because of that suffer from many diseases.